2021
DOI: 10.3390/healthcare9070915
|View full text |Cite
|
Sign up to set email alerts
|

Role of Laboratory Medicine in SARS-CoV-2 Diagnostics. Lessons Learned from a Pandemic

Abstract: Since the 2019 novel coronavirus outbreak began in Wuhan, China, diagnostic methods in the field of molecular biology have been developing faster than ever under the vigilant eye of world’s research community. Unfortunately, the medical community was not prepared for testing such large volumes or ranges of biological materials, whether blood samples for antibody immunological testing, or salivary/swab samples for real-time PCR. For this reason, many medical diagnostic laboratories have made the switch to worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Some of these techniques are already commercially available, such as Vizilite and VelScope, and their accessibility also depends on the possibility to be purchased from health facilities, even by smaller ones. Moreover, these techniques reflect the current trend in healthcare toward artificial intelligence that can successfully transform medical images analysis in pathology, radiology and other fields of medical imaging [85][86][87]. A review published in 2018 by Yang et al [45] on noninvasive diagnostic adjuncts for OPMDs evaluation showed that these techniques presented poor diagnostic accuracy due to high false-positive results [45].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these techniques are already commercially available, such as Vizilite and VelScope, and their accessibility also depends on the possibility to be purchased from health facilities, even by smaller ones. Moreover, these techniques reflect the current trend in healthcare toward artificial intelligence that can successfully transform medical images analysis in pathology, radiology and other fields of medical imaging [85][86][87]. A review published in 2018 by Yang et al [45] on noninvasive diagnostic adjuncts for OPMDs evaluation showed that these techniques presented poor diagnostic accuracy due to high false-positive results [45].…”
Section: Discussionmentioning
confidence: 99%
“…The principle of this method is the activity of endoribonuclease Cas with an sgRNA (single guide RNA) complex followed by probing of the amplified specific fragments of the virus. The test can be designed according to the measurement of fluorescence or lateral flow [ 10 , 11 ]. COVID-19 diagnosis uses the Cas-13 enzyme, which has the ability to react with RNA; after reverse transcription, the Cas12 or Cas9 enzyme possibly interacts with cDNA [ 10 ].…”
Section: Methods Typesmentioning
confidence: 99%
“…20 Maintaining a sufficient supply of high-quality PPE, coupled with continuous communication and updates on safety protocols, contributes to a secure working environment. 8 By prioritizing the safety of clinical laboratory personnel, healthcare systems can bolster their resilience during pandemics, safeguarding the well-being of essential frontline workers crucial to the diagnostic and monitoring processes.…”
Section: Personnel Safetymentioning
confidence: 99%
“…The ability to process large volumes of tests efficiently has been essential for implementing widespread screening programs and conducting surveillance activities. 8 Clinical laboratories have also been at the forefront of research efforts to understand the virus's characteristics, transmission dynamics, and impact on human health. 9 Through molecular biology techniques, serological assays, and genomic analyses, laboratories have contributed valuable insights into the virus's behavior, the development of immunity, and the emergence of variants.…”
Section: Introductionmentioning
confidence: 99%